Collisions & biases: estimating the impact of low-voltage distribution lines on the Ludwig's Bustard (Neotis ludwigii) - Schutgens, Maurice (FitzPatrick Institute of African Ornithology, 2023)
Bird collision mortality associated with power lines is a global conservation challenge. The Ludwig's Bustard (Neotis ludwigii) population is probably declining throughout its range as a result of collisions with power lines. Collision estimates derived from periodic carcass counts along power lines are likely to be underestimates because of two main bias factors: scavenger and search bias. In this study 44 Egyptian geese (Alopochen aegyptiacus) and Spurwing geese (Plectropterus gambensis) were used as surrogates to explore the levels of the bias by conducting a scavenger trial (90-day period) and three search trials (conducted after 24 hours, 48 and 90 days). Scavengers had detected 88% and removed 11 % of carcasses after the first week, and only 14% of carcasses were removed by the end of the 90-day trial period. On average, observers located 70% of carcasses across the three trials with no clear pattern in detection rate over time. Scavenger bias and search bias for this site in the Karoo were calculated at 0.14 and 0.30 respectively. Five low-voltage distribution power line transects (approximately 99 km) were surveyed in the Namakwa District, South Africa, to calculate a crude collision rate for Ludwig's Bustard. A total of 22 Ludwig's Bustard carcasses were located and used to estimate an unadjusted collision rate of 0.27 km-1. / (95% Cl 0.03-0.29 km-1. /). This collision rate extrapolated across the 63,000 km of distribution lines crossing the bustard's range represents an annual mortality of 13,000 individuals. The bias adjusted collision rate estimate increased to 0.45 km-1 ./ (95% CI 0.04-0.48 km-1 f 1 ), which suggests 22,000 individuals are killed annually. The combined mortality of low-voltage and high voltage lines could be in the order of 32 000 individuals annually. Implementation of existing mitigation devices and research into additional measures are necessary to prevent further decreases of this endangered species.